Estrategia de marketing y la promoción turística de la comunidad Shuyun Tsachila, cantón de Santo Domingo, año 2019 - Acosta Benavides, Karla Cristina (2020)
This research begins by describing the current tourist reality of the canton of Santo Domingo, the main objective of this strategic marketing plan is to design strategies to promote its tourist attractions in general in the Shuyun Tsachila community, seeking to encourage and improve tourist activity. The implementation of a strategic marketing plan to promote tourism will contribute to the growth of the canton of Santo Domingo in the social and economic sphere, causing the project to have a positive impact on the population of Santo Domingo. It is necessary to have the full support of its main authorities so that the strategic objectives set forth in the project are successfully carried out and the expected results are achieved. First, the general aspects of the canton were determined, such as the geographical delimitation, climate, population, among others; likewise, an analysis of the current situation of tourism in this sector was carried out, as well as a study of its attractions, plant and tourist infrastructure to have a vision of the tourist situation in which the Canton is located. The methodology used in this research is descriptive and synthetic analytical. Then, a market study was carried out to find out the main needs, requirements of tourists and owners related to the tourism business sector, which is why surveys and interviews were applied as research techniques. To finish, this research work designs a strategic plan which will be composed of positioning strategies, public relations and marketing mix to help the promotion and advertising of tourism in the canton of Santo Domingo.